2008
DOI: 10.1111/j.1349-7006.2008.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

MAGE‐C1/CT‐7 expression in plasma cell myeloma: Sub‐cellular localization impacts on clinical outcome

Abstract: Plasma cell myelomas (PMs) have a poor prognosis. Cancer-testis (CT) antigens are immunogenic proteins, representing potential targets for tumor vaccination strategies. The expression of the CT antigens GAGE, MAGE-A4, MAGE-C1/CT-7, and NY-ESO-1 was investigated on paraffin-embedded bone marrow biopsies from 219 PM and 8 monoclonal gammopathy of undetermined significance (MGUS) patients. The frequency and prognostic impact of these CT antigens were compared with known morphological prognostic markers (i.e. Mib1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 25 publications
(34 reference statements)
2
39
0
8
Order By: Relevance
“…30 Also, GAGE1 and CTAG1B immunoreactivity is both nuclear and cytoplasmic, whereas MAGEC1 immunoreactivity is only cytoplasmic without nuclear expression. 20,48 In conclusion, we found an early loss of cancer testis antigen expression (MAGEA3, MAGEA4, MAGEC1, GAGE1 and CTAG1B) in intratubular germ cell neoplasia and a re-expression in a subset of classic seminomas in contrast to spermatocytic seminomas, which were strongly positive for the cancer testis antigens mentioned above. We provide evidence that there are different phenotypic patterns of tumorigenesis in classic and spermatocytic seminomas.…”
Section: Discussionmentioning
confidence: 52%
“…30 Also, GAGE1 and CTAG1B immunoreactivity is both nuclear and cytoplasmic, whereas MAGEC1 immunoreactivity is only cytoplasmic without nuclear expression. 20,48 In conclusion, we found an early loss of cancer testis antigen expression (MAGEA3, MAGEA4, MAGEC1, GAGE1 and CTAG1B) in intratubular germ cell neoplasia and a re-expression in a subset of classic seminomas in contrast to spermatocytic seminomas, which were strongly positive for the cancer testis antigens mentioned above. We provide evidence that there are different phenotypic patterns of tumorigenesis in classic and spermatocytic seminomas.…”
Section: Discussionmentioning
confidence: 52%
“…12 Also GAGE1 and CTAG1B (NY-ESO-1) immunoreactivity is both nuclear and cytoplasmic, whereas MAGEC1 immunoreactivity is only cytoplasmic without nuclear expression. 6,23 In contrast, the MAGEC2 antibody showed an exclusive nuclear staining pattern. The staining was very intense, distinct and with little background so that cells expressing MAGEC2 was unmistakable.…”
Section: Discussionmentioning
confidence: 86%
“…32,33 In addition, recent findings had suggested that an increased expression of MAGE-C1/CT7 or MAGE-A3 in MM patients was associated with a higher proportion of proliferating plasma cells in the bone marrow. 11,15 Finally, microarray analyses of MM samples had suggested an association between CT antigen expression and the expression of proliferation-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, MM probably represents the malignancy with the richest CT antigen expression of all human cancers and the two CT antigens most frequently expressed in MM are MAGE-A3 and MAGE-C1/CT7. [10][11][12][13][14][15] MAGE-A3 is also expressed in a wide variety of solid tumors. It is a cytoplasmic protein with a molecular weight of 35 kDa 16 which was discovered analyzing CD8 + T-cell reactivity of a cancer patient against an autologous melanoma cell line.…”
Section: Introductionmentioning
confidence: 99%